2003
DOI: 10.1159/000071951
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cerebral Mitochondria during Acute Hypoglycemia

Abstract: To test the hypothesis that acute hypoglycemia leads to free radical induced alterations in cerebral mitochondria, newborn piglets were subjected to 2 h of insulin-induced hypoglycemia (blood glucose 1 mmol/l). The effects of free radicals were determined in cerebral cortical synaptosomes, mitochondria, and neuronal nuclei by measuring membrane lipid peroxidation. Fragmentation of nuclear and mitochondrial DNA was also examined. Lipid peroxidation was significantly increased in hypoglycemic mitochondrial membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…28 Subsequent work also shows neuronal hypoglycemia induces marked increases in both mitochondrial superoxide and hydrogen peroxide production. 29, 30 Further work using inhibitors of the mitochondrial ETC and measurements of specific activity levels of components of the ETC will be necessary to determine the exact ETC sources of mitochondrial ROS under low glucose conditions.…”
Section: Discussionmentioning
confidence: 99%
“…28 Subsequent work also shows neuronal hypoglycemia induces marked increases in both mitochondrial superoxide and hydrogen peroxide production. 29, 30 Further work using inhibitors of the mitochondrial ETC and measurements of specific activity levels of components of the ETC will be necessary to determine the exact ETC sources of mitochondrial ROS under low glucose conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased free radical generation, a 50-60% decrease in brain ATP and phosphocreatine levels has been demonstrated in the newborn piglet model of hypoglycemia used to test this hypothesis [55] . These studies were done with the piglet under general anesthesia.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…However, few large systematic studies have been conducted to characterize the association of neonatal hypoglycemic brain injury with infantile spasms. The lack of glucose can selectively impair multiple brain regions, including the superficial cortex, dentate gyrus, hippocampus, and caudate putamen; this impairment occurs through several putative mechanisms, such as the release of excitatory neurotransmitter (19), increased mitochondrial free radical generation and initiation of apoptosis (20), activation of neuronal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (21), and altered cerebral energetic characteristics (22,23). In one study in which the etiology of remote symptomatic epilepsy with onset during the first 3 years of life was examined, it was observed that neonatal hypoglycemia was the most common etiology, and infantile spasms were the most common type of seizure (14).…”
Section: Discussionmentioning
confidence: 99%